2021
DOI: 10.3390/molecules26092665
|View full text |Cite
|
Sign up to set email alerts
|

β-Boswellic Acid Inhibits RANKL-Induced Osteoclast Differentiation and Function by Attenuating NF-κB and Btk-PLCγ2 Signaling Pathways

Abstract: Osteoporosis is a systemic metabolic bone disorder that is caused by an imbalance in the functions of osteoclasts and osteoblasts and is characterized by excessive bone resorption by osteoclasts. Targeting osteoclast differentiation and bone resorption is considered a good fundamental solution for overcoming bone diseases. β-boswellic acid (βBA) is a natural compound found in Boswellia serrata, which is an active ingredient with anti-inflammatory, anti-rheumatic, and anti-cancer effects. Here, we explored the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…TNF-α can decrease the efflux of cholesterol in mouse osteocyte cell line MLO-Y4 by inhibiting the expression of ABCA1 [ 44 ]. Nuclear factor-κB (NF-κB) and receptor activator of NF-κB ligand (RANKL) have been implicated in osteogenic inhibition and osteoclast differentiation, promoting the development of OP [ 45 ]. Thus, it can be postulated that upregulation of ABCA1 may exhibit protective activities against OP by promoting cholesterol efflux.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α can decrease the efflux of cholesterol in mouse osteocyte cell line MLO-Y4 by inhibiting the expression of ABCA1 [ 44 ]. Nuclear factor-κB (NF-κB) and receptor activator of NF-κB ligand (RANKL) have been implicated in osteogenic inhibition and osteoclast differentiation, promoting the development of OP [ 45 ]. Thus, it can be postulated that upregulation of ABCA1 may exhibit protective activities against OP by promoting cholesterol efflux.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al found that β-boswellic acid (βBA), a natural compound found in Boswellia serrata , significantly inhibited the phosphorylation of Btk and PLCγ2. It also reduced the expression of NFATc1 at both mRNA and protein levels, resulting in the attenuation of osteoclast differentiation and formation (Park et al 2021 ). Jeong et al discovered that betulinic acid (BA), a natural plant-derived pentacyclic triterpenoid compound, effectively inhibited osteoclastogenesis by suppressing the phosphorylation of the PLCγ2-Ca 2+ signaling pathway (Jeong et al 2020a ).…”
Section: The Ca 2+ -Related Co-stimulation Signali...mentioning
confidence: 99%
“…Absorbance was measured at 450 nm at 1-h intervals. The sample treatment period was determined based on previous studies (21)(22)(23).…”
Section: Collection Of Bone Marrow-derived Macrophages (Bmm)mentioning
confidence: 99%